Drought-driven respond of fast and slow growing components of an adapted clover Rhizobium strain - Pacsuta, Péter; Ködöböcz, László; Biró, Borbála (Acta Biologica Szegediensis, 2005)
Drought tolerance of a selected Rhizobium leguminosarum bv. trifolii strain was tested in different, representative Hungarian soils in vitro. The stress-adapted strain (Zh-15) was isolated from the active root-nodules of the white clover (Trifolium repens L) grown in the highly salinic soil at Zám natural reserved area, Hungary. The water holding capacities (VK) of two sandy, calcareous and two, clayey, acidic soils was estimated and different water levels 30% (drought) and 60% ratio (optimum) of the total VK values was maintained for three weeks. The sterilised soils were inoculated preliminary with rhizobium suspension at a level of 106 cfu. g-1 soils. A selective plate counting method, modified in the lab. (Angerer et al. 1998) was used to assess the bacterium abundance in the soil. The survival of the drought-tolerant Zh-15 strain was highly depended on the soil characteristics on a certain water level. Clayey soils were found to protect the inoculums more efficiently, in comparison with the sandy soils. Such a modified cell-count, however, revealed that there are slow- and fast-growing components of the used, homogenous Rhizobium population. The fast growing, large colonies (“r” strategists) and the slow growing, tiny colonies ("k" strategists) had distinct survival capacities in the soils. The “k”-type cells were found to be more dependent on the soil characteristics, with an opposite survival tendency in the sandy or the clayey soils. This finding may outline the consideration of the strain- and soil characteristics, when designing microbial inoculums. The enumeration of the “r” and “k” strategist microbes, as introduced or indigenous in the soils, can be a new alternative in the environmental monitoring and eco-toxicology.